1,25-Dihydroxyvitamin D3 rapidly stimulates the solvent drag-induced paracellular calcium transport in the duodenum of female rats - Kukiat Tudpor (2018)
A calcium-regulating hormone 1α,25-dihydroxyvitamin D3 (1,25-[OH]2D3) has been known to rapidly stimulate the transcellular active calcium transport in the chick duodenum. However, its effects on the solvent drag-induced paracellular calcium transport, which normally contributes ∼70% of the total active calcium transport, and the underlying mechanism were unknown. The present study aimed to investigate the rapid nongenomic actions of physiological concentrations of 1,25-(OH) 2D3, i.e., 1, 10, and 100 nmol/l, on the duodenal calcium absorption in female rats. Quantitative real-time PCR revealed strong expressions of the classical vitamin D receptor (VDR) and the membrane-associated rapid response steroid binding receptors (MARRS) in both small and large intestines. By using the Ussing chamber technique, we found that duodenal epithelia acutely exposed to 10 and 100 nmol/l 1,25-(OH) 2D3 rapidly increased the solvent drag-induced calcium transport, but not the transcellular calcium transport, in a dose-response manner. On the other hand, 3-day daily injections of 1,25-(OH)2D 3 enhanced the transcellular active duodenal calcium transport. The 1,25-(OH)2D3-stimulated solvent drag-induced transport was abolished by the phosphatidylinositol 3-kinase (PI3K) inhibitors, 200 nmol/l wortmannin and 75 μmol/l LY294002, as well as PKC (1 μmol/l GF109203X) and MEK inhibitors (10 μmol/l U0126). Although 100 nmol/l 1,25-(OH) 2D3 did not alter the transepithelial mannitol flux, indicating no widening of the tight junction, it decreased the transepithelial resistance and increased both sodium and chloride permeability through the paracellular channel. We conclude that 1,25-(OH)2D3 uses the nongenomic signaling pathways involving PI3K, PKC, and MEK to rapidly enhance the solvent drag-induced calcium transport, partly by altering the charge-selective property of the duodenal epithelium at least for the pathways involving PI3K and MEK.